2021
DOI: 10.1016/j.surge.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of orthopaedic trauma patients undergoing surgery during the peak period of COVID-19 infection at a UK major trauma centre

Abstract: Background To review the clinical outcomes of all patients undergoing emergency orthopaedic trauma surgery at a UK major trauma centre during the first 6 weeks of the COVID-19 related lockdown. Methods A retrospective review was performed of all patients who underwent emergency orthopaedic trauma surgery at a single urban major trauma centre over the first six-week period of national lockdown. Demographics, co-morbidities, injuries, injury severity scores, surgery, COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…The low 30-day mortality rate of our patient cohort during the first COVID-19 peak is similar to figures published by Sobti et al, [10] Karayiannis et al, [11] Price et al, [12] Hope et al [13] and Giorgi et al [14] (2.3% v. 4.3%, 1.9%, 3%, 4% and 4.6%, respectively), and is considerably lower than mortality rates reported in other regions in the UK and other developing countries (11.76% -53%). [5,[7][8][9]13] The specific reasons for this lower mortality rate are not clear from our study, but may be attributed to an overall younger population undergoing surgery in our academic hospital and many lower-risk procedures being performed during this timeframe. We show that surgery was, for the most part, safely conducted despite the risk of SARS-CoV-2 infection and postoperative complications.…”
Section: Researchsupporting
confidence: 91%
See 2 more Smart Citations
“…The low 30-day mortality rate of our patient cohort during the first COVID-19 peak is similar to figures published by Sobti et al, [10] Karayiannis et al, [11] Price et al, [12] Hope et al [13] and Giorgi et al [14] (2.3% v. 4.3%, 1.9%, 3%, 4% and 4.6%, respectively), and is considerably lower than mortality rates reported in other regions in the UK and other developing countries (11.76% -53%). [5,[7][8][9]13] The specific reasons for this lower mortality rate are not clear from our study, but may be attributed to an overall younger population undergoing surgery in our academic hospital and many lower-risk procedures being performed during this timeframe. We show that surgery was, for the most part, safely conducted despite the risk of SARS-CoV-2 infection and postoperative complications.…”
Section: Researchsupporting
confidence: 91%
“…The research for this study was done in partial fulfulment of the requirements for RW's PhD degree at the University of Cape Town. Price et al [12] Retrospective, single-centre observational cohort study Hope et al [13] Retrospective review 23 March -4 April 2020 76 10 ( 13) 3 ( 4)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also found higher intensive care unit (ICU) admission and mortality rates after elective surgery on asymptomatic COVID-19 patients (18,19). A retrospective study indicated higher mortality and complications rates in patients with active COVID-19 who were over 70 years of age with orthopaedic trauma surgery (20). Furthermore, study of patients admitted to Pennsylvania trauma centers showed that traumatic injury concomitant with COVID-19 infection may increase risks of morbidity and mortality (21).…”
Section: Introductionmentioning
confidence: 98%
“…Patients with comorbid conditions including hypertension, diabetes and pulmonary disease are highly represented among hospitalised patients with COVID-19 disease, suggesting the presence of risk factors that may predispose heightened susceptibility to SARS-CoV-2 infection (25). In the literature there are several studies highlighting that mortality and the risk of developing post-surgical complications increase if there are concomitant comorbidities or an older age (>70 years) in COVID-19 patients (26,27) undergoing surgical procedures. Nonetheless, this topic is still a matter of debate, as some authors like Vranis and colleagues showed a mortality rate of 10% and a rate of Intensive Care Unit admissions of 18% after surgery, suggesting that patients COVID-19 undergoing surgery do not appear to have a significantly increased risk of mortality with respect to non-surgical COV-ID-19 patients.…”
Section: Discussionmentioning
confidence: 99%